Evaluation of Examination Scores by Using Standard Score Methods: A Case Study. - Sokkalingam, Rajalingam; Tan, Chong (INTI International University,Malaysia, 2011)
The marks or scores obtained by a student in an examination are raw scores. According to the authors proper decision and conclusion cannot be drawn on the basis of these raw scores because present scale of examination is full of deficiencies and errors. This scale is too approximate and we cannot measure the achievements of students in true sense. Therefore the authors suggest an alternative and effective way to evaluate the achievements of students that is known as standard score method. A case study was conducted to evaluate the achievements of two different batches of students in Mathematics units by using the standard scores method. The results show that the standard scores method is a better and more accurate method to measure the achievements of the students compared to the traditional method of giving marks in percentage. Finally the authors conclude that the method cannot identify which batch of students achievements better but can identify which group of students achievements better or poor within the batches and standard score method also can be used to determine the comparative achievement of those students who scored identical marks in both semesters.